Enhancing Indonesian Language Skills Through Cooperative Learning Model at MIS Al-Ihya 2 Cihaur - Siti nurlaela; Santi sardi (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This Classroom Action Research (CAR) aims to explore the effectiveness of the Cooperative Learning model in enhancing Indonesian language skills at MIS Al-Ihya 2 Cihaur. The study seeks to investigate how cooperative learning, which emphasizes collaboration and interaction among students, can improve their proficiency in Bahasa Indonesia, particularly in areas such as reading comprehension, writing, and speaking. The research was conducted in two cycles, with each cycle involving the stages of planning, implementation, observation, and reflection. Data was collected through classroom observations, student assessments, and interviews with both students and teachers. The findings indicate that the use of cooperative learning strategies significantly increased student engagement, improved language skills, and fostered a positive learning environment. Through group activities such as discussions, peer tutoring, and joint problem-solving tasks, students were able to work together, share knowledge, and learn from each other. This collaborative process helped to develop both cognitive and social skills. Additionally, students reported feeling more motivated and confident in their language abilities as they actively participated in group activities. The study concludes that the Cooperative Learning model is an effective teaching method for improving Indonesian language proficiency at the primary school level. It provides an inclusive, interactive, and student-centered learning environment that caters to diverse learning needs. This research contributes to the growing body of knowledge on cooperative learning and offers valuable insights for educators seeking to implement this model in enhancing language education in Indonesian schools.